Management of Peri-Implantitis: Current Approaches and Future Direction - Zahra Mohammed Hassan Maran; Abdullah Mufarrih AlGahtani; Aisha Abdullah AlAssiri; Sheikah Mohammad Albreek; Monirah Zaid Alaqeeli; Reem Mohammed Alhowel; Alhanouf Nasser Alabdullah; Mohammad osama ghannam; Nuha Abdullah Rashid Alnemer; Feras hamoud alshehri; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Dental implants have become a widely accepted treatment option for tooth replacement, but their long-term success can be compromised by peri-implantitis, a progressive inflammatory condition affecting the supporting tissues around implants. Peri-implantitis is characterized by progressive bone loss and can potentially lead to implant failure if not properly managed. This paper provides a comprehensive overview of the current approaches to managing peri-implantitis, including risk factor identification, non-surgical and surgical treatment modalities, and potential future directions. Several local and systemic factors, such as implant surface characteristics, excess cement, smoking, history of periodontitis, diabetes, and osteoporosis, have been associated with an increased risk of peri-implantitis development and progression. Non-surgical management, involving mechanical debridement, antimicrobial therapy, and chemical decontamination, aims to disrupt biofilms and reduce inflammation. Surgical interventions, including open flap debridement, regenerative procedures, implantoplasty, and resective surgery, may be necessary for advanced cases. Ongoing research efforts are exploring adjunctive therapies, such as antimicrobial photodynamic therapy, probiotics, bioactive molecules, and implant surface modifications, as well as preventive strategies and risk factor management. The identification of reliable biomarkers and the development of targeted therapies based on molecular diagnostics hold promise for improving early detection and personalized treatment approaches. A multidisciplinary approach combining preventive measures, appropriate interventions, and continued research is crucial for addressing the challenges of peri-implantitis and ensuring the long-term success of dental implants.